Use of Early Clinical Trial Data to Support Thorough QT Study Waiver for Upadacitinib and Utility of Food Effect to Demonstrate ECG Assay Sensitivity. Issue 5 (25th September 2017) - Mohamed, Mohamed‐Eslam F.; Zeng, Jiewei; Jiang, Ping; Hosmane, Balakrishna; Othman, Ahmed A.
Abstract : Exposure–response analyses of QT data from early‐stage clinical studies represent a valuable tool to assess the QT prolongation potential for drugs in development in lieu of standalone thorough QT (TQT) studies. However, demonstrating adequate electrocardiogram assay sensitivity can be challenging in the absence of a positive pharmacological control. Upadacitinib is a Janus kinase 1 inhibitor currently being evaluated in phase III rheumatoid arthritis trials. Exposure–response analyses to evaluate the QT prolongation potential for upadacitinib from phase I trials and the utility of the effect of food on QTcF to demonstrate ECG assay sensitivity are presented. The analyses demonstrated no effect of upadacitinib on QT interval and confirmed the sensitivity of the ECG assay to detect the small QT shortening effect caused by food. Lack of bias from manual ECG adjudication was also demonstrated. These analyses supported requesting a waiver for the regulatory requirement for a dedicated thorough QT study for upadacitinib.